2009
DOI: 10.1159/000203124
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Contrast Agents in Ischemic Stroke

Abstract: The general indication for the use of ultrasound contrast agents in neurosonologic applications is an insufficient signal-to-noise ratio when investigating the cerebral macro- and microcirculation. Clinical problems that are often encountered in native sonography are ‘no flow, slow flow and low flow’ phenomena. In these cases, ultrasound contrast agents are used to differentiate between vessel occlusion and insufficient insonation conditions, as well as for the detection of very slow blood flow velocities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 141 publications
(114 reference statements)
0
29
0
2
Order By: Relevance
“…The addition of an ultrasound contrast agent allows adequate diagnosis in about 80–90% of patients with insufficient bone windows [12,13,14,15,16,17,18,19,20]. In our Japanese stroke patients, 40% of TBWs had an improved detection of the M1 on contrast-enhanced examination.…”
Section: Discussionmentioning
confidence: 91%
“…The addition of an ultrasound contrast agent allows adequate diagnosis in about 80–90% of patients with insufficient bone windows [12,13,14,15,16,17,18,19,20]. In our Japanese stroke patients, 40% of TBWs had an improved detection of the M1 on contrast-enhanced examination.…”
Section: Discussionmentioning
confidence: 91%
“…Optional use of an ultrasound contrast agent (SonoVue®, Bracco Imaging SpA, Milan, Italy) allowed us to increase our diagnostic confidence in cases of inferior transcranial bone windows and to save examination time [12]; it also proved valuable during examinations made difficult during emergency transport. Intravenous injections of 0.5–2 ml contrast agent were administered, depending on the quality of the temporal bone window as previously described [13].…”
Section: Methodsmentioning
confidence: 99%
“…In transcranial applications, however, some patients' temporal windows are impenetrable without a contrast agent due to attenuation by the skull. Many researchers have found that the use of a contrast agent can salvage most otherwise non-diagnostic exams so that a diagnosis may be made for virtually all patients [16].…”
Section: Doppler-based Techniquesmentioning
confidence: 99%